Exploring the Transferability of STEM PBL Instructional Principles from Higher Education to K-12 Classrooms - Ali Bicer; Tugce Aldemir; Trina J. Davis; Jamaal Young (Education Sciences)
The first objective of this study was to explore which principles of STEM PBL instruction pre-service teachers found most beneficial in enhancing their understanding of mathematics- and science-related concepts. The second objective was to identify the instructional practices from STEM PBL that pre-service teachers intended to incorporate into their future teaching practices. We conducted a descriptive qualitative study, analyzing data from interviews (n = 8), reflections, and classroom artifacts (ntotal = 43). The findings revealed 12 distinct themes: six associated with the first objective and six linked to the second objective. Two themes—communication and real-world relevance—emerged as common across both objectives. The significance of this study lies not only in identifying key principles of STEM PBL but also in highlighting the need to emphasize these principles in various instructional methods, enhancing the transferability of innovative practices to future teachers’ mathematics classrooms.